Analisa Strukturmikro dan Pengaruhnya terhadap Sifat Mekanis Batangan Rel Tipe R54 [Microstructure Analysis and Its Effect to Mechanical Properties of Rail Track Type R54] - Dwiwandono, Robby; Firmansyah, Leksono; Herbirowo, Satrio; Hasbi, M Yunan; Citrawati, Fatayalkadri (Jurnal Metalurgi, 2017)
This study was conducted to observe the mechanical properties and microstructures of two rail tracks type R54 used in Indonesia, which produce in Germany (rail steel G) and China (rail steel C). During its application, it is necessary for rail track to have high toughness to bear the dynamic load from wheel movement. In this study, several examinations and observations have been made, which comprise OES chemical composition analysis, metallography by using OM, tensile test, and micro Vickers hardness test. The OES chemical composition result shows that both rail tracks belong to Fe-C-Mn rail steels, in which, rail steel G has higher Zr micro alloy content than rail steel C. These differences do not significantly affect their tensile strength, which are 1050 MPa and 1044 MPa for rail steel G and rail steel C, respectively. Moreover, both samples were observed to have elongation of 13%. The difference in micro alloys, specifically Zr, may influence the hardness of the samples through precipitate strenghtening. The average hardness in the body part of the tracks show that rail steel G has slightly higher hardness value compare to rail steel C. It is 341 HV for rail steel G and 324 HV for rail steel C. This hardness difference was also found between the head part and the body part of both rail tracks. In the head part, the area near the edge of the rail tracks e has an average hardness of 452 HV for rail steel G and 423 HV for rail steel C. These values are higher than the hardness value of the body part of both rail tracks. The difference in hardness of the body part and the head part might be due to the phases in their microstructure, which observed to be dominated by pearlite.